Optimizing steel plate shear wall performance: influence of infill plate thickness and connection length to vertical boundary elements / Saidatul Assyura Rosman ... [et al.] - Rosman, Saidatul Assyura; Ramli, Mohd Zamri; Mohd Fisol, Muhammad Farhan; Zulhazmi, Nur Izzaty (2024)
The Steel Plate Shear Wall (SPSW) is widely used as a lateral force resisting system in areas prone to high seismic activity. This is because of its exceptional ductility and ability to dissipate energy. Previous studies have indicated that disconnecting the infill plate from the Vertical Boundary Element (VBE) can decrease the demands on the column. The observed outcomes lead to a decline in both the energy dissipation capability and the lateral load-bearing capacity. The primary goal of this investigation is to mitigate stress on the column while concurrently reducing both the energy dissipation and lateral force capacities. To accomplish this, a partial connection will be established between the infill plate and the Vertical Boundary Element. Thus, the overarching objective of this research is to identify the optimal connection length that minimizes the demands on the column while simultaneously curtailing the reduction in energy dissipation and lateral force capacities. Using Abaqus software, twenty models with different infill plate thicknesses and lengths of connection between the infill plate and Vertical Boundary Element were analysed. To determine the optimal length of connection between the infill plate and Vertical Boundary Element, the energy dissipation capacity, lateral load capacity, and column stresses were evaluated and compared. The maximum dissipation of energy occurs at a connection length of 75% between the infill plate and Vertical Boundary Element and an infill plate thickness of 12 mm. In contrast, the greatest lateral load capacity is achieved at connection lengths of 50% between a 25 mm infill plate thickness and a Vertical Boundary Element weight of 25%. The column stress reaches its minimum value when the infill plate measures 20 and 25 mm, and it reaches its maximum value when the infill plate measures 6 mm and 12 mm. By increasing the thickness of the infill plate and minimizing its connection to the Vertical Boundary Elements, the column stress in Vertical Boundary Elements can be decreased, while simultaneously enhancing lateral load capacity and maintaining an adequate level of energy dissipation.